Metode Life Cycle Assessment (LCA) Sebagai Penilaian Terhadap Dampak Lingkungan pada Proses Produksi Pupuk ZA II Petrokimia Gresik - Aussie Amalia; Bagas Chrisma Pratama (Prosiding ESEC, 2023)
Petrokimia Gresik is one of the largest and most comprehensive fertilizer companies in  Indonesia, playing a major role in the food security sector. The superior fertilizer production is  ZA II fertilizer. The existence of a strong concern lies in the emissions produced in the production  process where the presence of gas can trigger environmental impacts if not properly managed and  controlled. Therefore, through methodLife Cycle Assessment (LCA) is able to identify and assess  potential environmental impacts in PT Petrokimia Gresik's ZA II fertilizer production process.  Approach done byEndpoint divided into human health, ecosystem quality, and natural  resourcesRecipe 2016. As a support for the identification carried out, software will be used in the  form of Open LCA type 1.11.0 and SimaPro type 9.4.0.2. The studies obtained show that there is  a unit process that is produced with the greatest impact on the drying unit system (drying) and  cooling (cooling) due to the causes of the chemicals used and the emission content released in the  form of ammonia (NH3) and carbon dioxide (CO2). With this impact, it is necessary to carry out  alternative solutions to reduce the risk of impacts that occur in the ZA II fertilizer production  process.